Analysis of Discourse at a Place of Work - Žic Fuchs, Milena (Array, 1981)
Analysis of office discourse between adult role-equals has not been attempted to date in Croato-Serbian. We suggest a possible coding system for such a discourse situation and analyse the varied ways in which people get others to do things ; the role of non-linguistic utterances ; the aincidence and kinds ofellipticality ; discourse cohesion ; the incidence and kinds of regulatives of person-to-person and person-to-world relations. This research is planned as a basis for future contrastive work in this field. Analiza diskursa između odraslih ljudi podjednakog društvenog statusa na radnom mjestu nije dosad provedena na hrvatskom ili srpskom jeziku. Autori predlažu jedan sustav kodiranja za takvu vrst diskursa i pružaju uvid u različite načine kojima se ljudi služe kako bi postigli da drugi nešto učine za njih ; uloga nejezičnih izričaja ; kohezija diskursa ; učestalost i vrste regulativa u odnosima: čovjek - čovjek i čovjek - svijet. Ovo istraživanje treba poslužiti kao polazište za planirani rad na kontrastiranju engleskog i hrvatskog ili srpskog diskursa.